DETERMINATION OF FLEET SIZE AND ASSIGNMENT OF TRAINS AND ROUTES BY MAXIMIZING THE NUMBER OF TRIPS - Cakmak, Emre; Yildiz, Feride Suheda; As, Yakup; Onden, Ismail (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
To advance a globally sustainable mobility paradigm, nations are increasingly prioritizing environmentally responsible transportation modes. Within this context, railway systems have assumed paramount significance, encompassing infrastructure development and operational efficiency. The challenge arises in optimizing capacity utilization while minimizing investment costs, given the limitations of available resources. This paper introduces an ingenious integer optimization model aimed at maximizing the frequency of train trips. Simultaneously, it determines the ideal composition of high-speed and conventional train fleets through empirical data analysis. What sets this study apart is its comprehensive approach, encompassing not only trip frequency but also the intricate dynamics of mixed train types, route assignments, and the identification of bottlenecks within railway segments. The findings affirm the model's effectiveness in addressing contemporary global challenges, highlighting its practical applicability.